Estimates of the Impact of COVID-19 on World Poverty in 2020 - Qader, Zaki Hussein; Salih, Twana Fadhil (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2022)
In this study we have sought to make estimates of the potential short-term poverty impact of COVID-19 in selected countries. While these estimates have important limitations as they are based on distribution neutral assumptions and crucially omit, social and fiscal policy, and household-level responses to economic contractions, they are intended as indicative of the potential increase in poverty as a result of the damaging economic consequences of the pandemic. The study concludes that there is a negative relationship between economic growth and poverty in the short run, where if economic growth changes by one unit, poverty decreases by (4.08). This is a logical result in light of the COVID- 19 epidemic. As for the other variables, such as the unemployment rate and inflation, their effect was positive, Also, the main variable of Confirmed cases with the virus to population, its impact was negative in the long run, while in the short run the impact is positive as stated in the economic theory, and this was expected in the research hypothesis, where the number of people infected with the virus increase, the poverty in the world increase in the same direction.
Keywords: الأمراض والأوبئة -- فيروس كورونا "كوفيد-19" -- التنمية الاقتصادية -- معدلات البطالة -- التضخم الاقتصادي